Relationship between Lower Limb Flexibility, Power, Agility and Speed in Football Players: A Cross-sectional Study - Tresha Parmar; Neha Mukkamala (Journal of Clinical and Diagnostic Research)
Introduction: Football is a complex game characterised by unpredictable movement patterns. 17% of injuries in football have been attributed to tightness in the hamstring muscles and a lack of flexibility. In football, the ability to quickly change direction, produce a high rate of power output, and sprint at high velocity is essential for optimal performance. The effect of lower limb flexibility and its relationship to skills required in football, such as agility, power, and speed, have not been previously studied. Aim: To examine the relationship between lower limb flexibility, power, agility, and speed in football players. Materials and Methods: This cross-sectional study was carried out in the football field of Sumandeep Vidyapeeth Deemed to be University, Vadodara, Gujarat, India on 30 male football players who played at Sumandeep Vidyapeeth campus from January 2021 to August 2021. Football players aged between 18 to 25 years who had been involved in regular football training sessions atleast three times per week for the past year were included in the study. Participants with a history of musculoskeletal injuries to the back, shoulder, elbow, or lower limb within the past six months, or those with any history of cardiorespiratory or neurological problems that could affect test performance, were excluded. Apart from anthropometric measurements, participants were assessed for flexibility using the Active Knee Extension Test (AKET) and the V-sit and reach test, agility using the Arrowhead Agility Test (AAT), power using the Vertical Jump Test (VJT), and sprinting ability using the 40-yard dash test. Correlations among flexibility, agility, power, and speed were assessed using Pearson’s correlation coefficient. Statistical significance was set at p-value<0.05. Results: Total 30 participants were recruited, with a mean age of 20±1.5 years and a mean Body Mass Index (BMI) of 22±1.7 kg/m². The mean active knee extension angle for the right-side was 25±1.9°, and for the left-side, it was 24.6±8.5°. The mean value for the sit and reach test was 42±1.5 cm, the vertical jump was 44±7.9 cm, the AAT was 9.1±1.5 seconds, and the 40-yard dash test was 6.5±0.91 seconds. A significant positive correlation was found between AKET and AAT (r=0.482, p-value=0.007) and between the V-sit and reach test (VSRT) and VJT (r=0.491, p-value=0.006). However, no statistically significant correlations were found between AKET and VJT, AKET and the 40-yard dash, AAT and VJT, or VJT and the 40-yard dash. Conclusion: A positive correlation was found between hamstring flexibility with agility and negative correlation was found between hamstring flexibility with power. There was no statistically significant correlation found between flexibility and sprint.